Itihāsakāra va prasiddha sāhittika Hari Nārāyaṇa Āpaṭe - Pānase, Veṇūbāī (Ānandāśrama Sãsthā, 2021)
On the life and works of Hari Narayan Apte, 1864-1919, Marathi author
Reprint. Originally published: 1931
Keywords: Biografie; Apte; Hari Narayan; Authors; Marathi